African American adults and seasonal influenza vaccination: Changing our approach can move the needle - Sandra Crouse Quinn (Taylor & Francis Group, 2018)
Consistent disparities in influenza (flu) vaccine uptake among African Americans, coupled with a disproportionate burden of chronic diseases, places too many African Americans at high risk for complications, hospitalizations and premature mortality. This disparity is the result of individual attitudes and beliefs, social norms, and health care practices. Recent research identifies critical factors affecting vaccine uptake among African American adults including perceived risk of vaccine side effects, social norms that do not support for vaccination, and lower knowledge of the flu and the vaccine. Yet in our nationally representative survey of African Americans, we also found that there is substantial trust in one's own physician about the flu vaccine coupled with valuing the provider's vaccine recommendation. Other recent research has found that African Americans are not receiving strong recommendations and specific offers of the vaccine in their health care visit. This commentary suggests particular roles and strategies for health care providers, public health agencies, and African American communities and families, which can literally move the needle to increase seasonal flu vaccination.